Parallel coordinates as tool of exploratory data analysis - Savoska, Snezana; Loshkovska, Suzana (My University, 2009)
The huge amount of multidimensional data everyday becomes bigger and more complex. For these reasons, data analysis of multivariate data becomes very difficult. In this paper, we present a visualization technique for multidimensional data sets named Parallel Coordinates as a technique for exploratory data analysis. The paper describes the technique and its applications. We present several examples of technique successful application as a tool for visual data analysis of the multivariate data.
Keywords: Parallel Coordinates, exploratory data analysis, multivariate visualization